Exploring the link between genetic disorders and early-onset periodontal disease - Balkhair, Ola Jamal; Badahdah, Rasha Ahmed; Alajmi, Almaram Abdullah; Almutairi, Khulud Mukhlid; Alqahtani, Atheer Mutlak; Alkhaldi, Hayfa Hmoud; Almotari, Nouf Safar; Alsharif, Haifa Mohammed; Almutairi, Sarah Hamad (International Journal Of Community Medicine And Public Health, 2025)
Periodontal disease is a complex, multifactorial condition characterized by chronic inflammation and progressive destruction of the tooth-supporting structures. Among its various forms, early-onset periodontitis is particularly aggressive and often associated with genetic predispositions. Genetic and epigenetic factors play pivotal roles in shaping host susceptibility to this disease by influencing immune responses, inflammatory regulation, and tissue homeostasis. Single-nucleotide polymorphisms (SNPs) in genes encoding cytokines, such as interleukin-1β and tumor necrosis factor-alpha, are linked to heightened inflammatory responses, amplifying tissue damage and accelerating disease progression. Additionally, polymorphisms in genes like TLR2 and TLR4 impair microbial recognition, promoting chronic inflammation and dysbiosis. Epigenetic modifications, including DNA methylation and histone acetylation, further modulate gene expression, contributing to the dynamic interplay between genetic predispositions and environmental factors like smoking or poor oral hygiene. Emerging research has also highlighted genetic markers such as human leukocyte antigen (HLA) alleles and matrix metalloproteinase (MMP) variants as predictors of disease severity and therapeutic outcomes. These insights have driven the development of targeted therapies, including inhibitors of pro-inflammatory mediators, MMP inhibitors, and potential miRNA-based interventions. High-throughput technologies, such as genome-wide association studies (GWAS), have expanded the understanding of genetic pathways involved in periodontal disease. These advances enable earlier disease detection and personalized treatment strategies, offering the potential to mitigate progression and reduce the burden of severe periodontitis. The integration of genetic and epigenetic research into clinical practice marks a significant step toward precision medicine, providing a framework for tailored prevention and therapeutic interventions aimed at improving patient outcomes. Future research must continue to explore these genetic mechanisms to uncover novel biomarkers and refine targeted treatment approaches for periodontal disease.